2011
DOI: 10.1007/s10725-011-9624-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycorrhizal inoculations on heavy metal uptake and stress alleviation of Cajanus cajan (L.) Millsp. genotypes grown in cadmium and lead contaminated soils

Abstract: The aim of the present study was to evaluate the role of arbuscular mycorrhizal (AM) fungi on metal uptake, oxidative effects and antioxidant defence mechanisms under cadmium (Cd) and lead (Pb) stresses in Cajanus cajan (L.) Millsp. (pigeonpea). Treatments consisted of two concentrations each of Cd (25 and 50 mg/kg of soil) and Pb (500 and 800 mg/kg of soil) singly as well as in combination. Both metals induced oxidative damage through increased lipid peroxidation, electrolyte leakage and hydrogen peroxide lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(32 citation statements)
references
References 68 publications
2
28
0
Order By: Relevance
“…It is interesting to note that the filter function of arbuscular mycorrhizal fungi (AMF), in the case of highly contaminated soils, dominates the literature, as for example in the works described by Meier et al (2012b) and Garg and Aggarwal (2012), most of the studies being performed in pot experiments. Conversely, some authors demonstrated that the inoculation of plants by AMF such as Glomus species significantly enhanced PTE translocation to the aboveground parts of plants (Meier et al, 2012a).…”
Section: Effects Of Mycorrhizal Inoculationmentioning
confidence: 99%
“…It is interesting to note that the filter function of arbuscular mycorrhizal fungi (AMF), in the case of highly contaminated soils, dominates the literature, as for example in the works described by Meier et al (2012b) and Garg and Aggarwal (2012), most of the studies being performed in pot experiments. Conversely, some authors demonstrated that the inoculation of plants by AMF such as Glomus species significantly enhanced PTE translocation to the aboveground parts of plants (Meier et al, 2012a).…”
Section: Effects Of Mycorrhizal Inoculationmentioning
confidence: 99%
“…Wei and Wang (1991) reported that Schizonepeta tenuifolia increased EO production, plant biomass and nutrient uptake significantly when these plants were inoculated with AMF. Garg and Aggarwal (2012) and Lermen et al (2015) observed that AMF are potentially able to minimize plant uptake of HMs such as Pb. However, this evidence is not the general rule because some plants do not respond to the AMF association.…”
Section: Chemical Identification Of Essential Oilmentioning
confidence: 99%
“…Exposure to Cd drives oxidative injuries, such as lipid peroxidation, which leads to alteration in the membrane functionality and protein carbonylation (Schützendübel et al, 2001;Romero-Puertas et al, 2002;DalCorso et al, 2008DalCorso et al, , 2010Garg and Aggarwal, 2012). A possible constitutive mechanism of detoxification in plants is upregulation of antioxidants such as superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), peroxidase (POX), and catalase (CAT) (Meharg, 2005;Gomes et al, 2012;Dave et al, 2013;Sobrino-Plata et al, 2014).…”
Section: Introductionmentioning
confidence: 99%